Research on Primary Health Nurses in Providing the Home-based Palliative and Hospice Care - Wenqian Bie; Marietta Fabros; Yexu Qiao (Journal of Medicine and Life Sciences, 2026)
As the population ages, demand for primary health care (PHC) will surge, straining China's healthcare system. Home-based PHC remains fragmented and faces barriers such as urban-rural disparities, workforce shortages, low public awareness, cultural taboos about death, and inadequate insurance coverage. Primary health nurses, who deliver care at home, encounter persistent challenges that affect care quality and their own well-being. This study systematically identified and analyzed these challenges to inform practice improvements and strategies for safer, more sustainable home-based palliative care. The findings have theoretical, practical, and policy implications for China's home-based palliative care development.